Demonstration of functional rehabilitation treatment effects in children and young people after severe acquired brain injury. (19th May 2022) - Forsyth, Rob; Hamilton, Colin; Ingram, Matthew; Kelly, Gemma; Grove, Tim; Wales, Lorna; Gilthorpe, Mark S
ABSTRACT: Purpose: To examine relationships between functional outcomes after pediatric acquired brain injury (ABI) and measures of rehabilitation dose. Methods: An observational study of children receiving residential neurorehabilitation after severe ABI. Results: Basic total rehabilitation dose shows a paradoxical inverse relationship to global outcome. This is due to confounding by both initial injury severity and length of stay, and variation in treatment content for a given total rehabilitation dose. Content-aware rehabilitation dose measures show robust positive correlations between fractions of rehabilitation treatment received and plausibly related aspects of outcome: specifically, between rates of recovery of gross motor function and the fraction of rehabilitation effort directed to active practice and motor learning. This relationship was robust to adjustment for therapists' expectations of recovery. Conclusion: Content-aware measures of rehabilitation dose are robustly causally related to pertinent aspects of outcome. These findings are step toward a goal of comparative effectiveness research in pediatric neurorehabilitation.